Immediate and subsequent effects of drying and rewetting on microbial biomass in a paddy soil. Issue 1 (2nd January 2019) - Sawada, Kozue; Funakawa, Shinya; Kosaki, Takashi
ABSTRACT: Many surface soils in Japan may experience more frequent and intense drying–rewetting (DRW) events due to future climate changes. Such DRW events negatively and positively affect microbial biomass carbon (MBC) through microbial stress and substrate supply mechanisms, respectively. To assess the MBC immediately after DRW and during the incubation with repeated DRW cycles, two laboratory experiments were conducted for a paddy soil. In the first experiment, we exposed the soil to different drying treatments and examined the MBC and hourly respiration rates immediately after the rewetting to evaluate the microbial stress. In the second experiment, we compared microbial growth rates during the incubation of the partially sterilized soil with a continuously moist condition and repeated DRW cycles to evaluate the contribution of the substrate supply from non-biomass soil organic C on MBC. First, all drying treatments caused a reduction in MBC immediately after the rewetting, and higher drying intensities induced higher reduction rates in MBC. A reduction of more than 20% in MBC induced the C-saturated conditions for surviving microbes because sufficient concentrations of labile substrate C were released from the dead MBC. Second, repeated DRW cycles caused increases in the microbial growth rates because substrate C was supplied from non-biomass organic C. In conclusion, MBC decreased immediately after DRW due to microbial stress, whereas MBC increased during repeated DRW cycles due to substrate C supplied from non-biomass organic C.